Determination of Crystallinity Ratio and Some Physicochemical Properties of Poly(4-methyl-1-pentene) - Yazici, O.; Cakar, F.; Cankurtaran, O.; Karaman, F. (WILEY, 2009)
It was determined that the thermal stability of poly(4-methyl-1-pentene) (P4MP) was maintained up to 424 degrees C in an inert atmosphere by thermogravimetric analysis. The retention diagrams of ethyl acetate, tert-butyl acetate, and benzene on P4MP were plotted at temperatures between 30 and 280 degrees C by inverse gas chromatography (IGC) technique. Melting temperature of the polymer was determined as 230 and 239.5 degrees C by IGC and differential scanning calorimetry (DSC), respectively. The percent crystallinity of P4MP was obtained from the retention diagrams at temperatures below melting point. The percent crystallinity obtained by IGC is in good agreement with the ones obtained by DSC. Then, specific retention volume, V-g(0), weight fraction activity coefficient, Omega(infinity)(1) Flory-Huggins polymer-solvent interaction parameter, chi(infinity)(12), equation-of-state polymer-solvent interaction parameter, chi(12)* and effective exchange energy parameter, X-eff of octane, nonane, decane, Undecane, dodecane, tridecane, n-butyl acetate, isobutyl acetate, isoamyl acetate with P4MP, were determined between 240 and 280 degrees C by IGC. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 901-906, 2009
Keywords: inverse gas chromatography; poly(4-methyl-1-pentene); percent crystallinity; thermodynamics; differential scanning calorimetry; STATISTICAL THERMODYNAMICS; GAS-CHROMATOGRAPHY; POLYCAPROLACTONE; MIXTURES; SOLVENTS; VOLUME; Polymer Science